Dynamic business english (California : DynEd International, 2000)
Dynamic business english ia a powerful and cost-effective solution for today's business english student.
part 1 Company description - part 2 Work experience - part 3 Manufacturing & trade - part 4 Product comparisons - part 5 Decision making - part 6 Planning ahead.
System requirements: Windows 95, 98 or Windows NT, Pentium 166 with 32MB of RAM (Pentium 200 recommended), 640 X 480 with high-color 16-bit display, quad-speed CD-ROM drive, 16-bit sound card and microphone.
Keywords: Business communication; English language -- Business English; Public speaking